Praxish: A Rational Reconstruction of a Logic-Based DSL for Modeling Social Practices - Dameris, James; Hernandez Roman, Rosaura; Kreminski, Max (Proceedings of the AAAI Conference on Artificial Intelligence and Interactive Digital Entertainment, 2023)
The Versu framework is historically notable for its full-featuredness as a suite of tools for creating highly responsive interactive dramas. However, it has also been lost for nearly a decade, and a similarly approachable and flexible simulationist interactive narrative authoring framework has not yet emerged to take its place. We therefore aim to introduce an open-source rational reconstruction of the Versu framework, drawing on publicly available documentation of Versu's design and implementation to assemble a successor system with similar architecture and capabilities. Here, we present the first component of this system: Praxish, a reconstruction of the low-level exclusion logic language atop which the rest of Versu's functionality is based.